Integrated STEM Approaches and Associated Outcomes of K-12 Student Learning: A Systematic Review - Hong Chung Le; Van Hanh Nguyen; Tien Long Nguyen (Education Sciences, 2023)
Educators and researchers are increasingly recognizing the potential benefits of integrated science, technology, engineering, and mathematics (STEM) education to improve students’ learning outcomes, including the learning achievements, interest in STEM, learning motivation, and higher-order thinking skills of K-12 students. While there is a considerable body of research on this topic, it lacks a comprehensive synthesis of the available evidence to provide a more rigorous and systematic understanding of the relationship between integrated STEM approaches and associated outcomes of K-12 student learning. Therefore, the purpose of this study was to examine the integrated STEM approaches and associated outcomes of K-12 student learning through a systematic literature review. The studies were accessed using the Scopus, ERIC, and Google Scholar databases in February 2022. A total of 47 studies were retained for inclusion in the review. We used the ecological triangulation method for data extraction and synthesis. A total of 23 ecological sentences developed from existing studies revealed that the associated outcomes of K-12 student learning occur differently when using different integrated STEM approaches. For example, STEM project-based learning activities in the science curriculum focused on improving students’ learning achievement and higher-order thinking skills, while out-of-school STEM project-based learning activities focused solely on students’ STEM career interests. Finally, we note several directions for future research related to student learning outcomes using integrated STEM approaches.